Islamic Banking and Fintech : Sustainable Collaboration Jel G21, G23 - Khairul Umam Khudhori; Loni Hendri (Al-Intaj)
This paper aims to conclude the best collaboration form between Islamic Banking and Syariah Fintech which is beneficial for both of them and also beneficial for customer. Descriptive-critical analysis is used in this paper. The analysis began by presenting collaboration forms between Bank and Fintech, then the forms are analyzed to find the most beneficial collaboration form for Islamic Banking, Syariah Fintech and customer.The result shows that the most beneficial collaboration form is collaboration between Islamic Banking and Syariah Fintech to increase financing services. By this form of collaboration, Islamic Banking could use the network of Syariah Fintech to channelize the financing to its customer which is untouchable before. This collaboration needs detail regulation and policy to protect every single entity included in it collaboration.